Honey on brain health: A promising brain booster - Nurul Ashykin Zamri; Nurhafizah Ghani; Che Aishah Nazariah Ismail; Rahimah Zakaria; Nazlahshaniza Shafin (Frontiers in Aging Neuroscience, 2023)
Since ancient times, honey has been employed in many aspects of everyday life, the most popular of which is as a natural sweetener. Honey is used not only as a nutritional product but also in health as a supplement and in various applications, especially related to brain booster health. Brain health is the capacity to carry out all mental functions necessary for cognition, such as learning and judging, utilizing language, and recalling. This review presents the current trend of research on honey, particularly the interest in underlying mechanisms related to brain booster health. A total of 34 original articles addressing brain health from the consumption of honey were analyzed. We identified four main brain health benefits, which are memory booster, neuroprotective effect, anti-stress, and anti-nociceptive potentials with the proposed underlying mechanism. A lot of attention has been paid to the role that honey plays in brain health research, with the goal of examining the link between honey and brain health as well as the mechanism underlying it, the findings from this review may be potentially beneficial to develop new therapeutic roles for honey to help determine the best and most promising to benefit and boost overall brain health.